2011
DOI: 10.1002/jemt.21074
|View full text |Cite
|
Sign up to set email alerts
|

Surface ultrastructure of the gill filaments and the secondary lamellae of the catfish,Rita rita, and the carp, Cirrhinus mrigala

Abstract: Surface ultrastructures of gill filaments and secondary lamellae of Rita rita and Cirrhinus mrigala, inhabiting different ecological habitat, were investigated to unravel adaptive modifications. R. rita is a sluggish, bottom dwelling carnivorous catfish, which inhabits regions of river with accumulations of dirty water. It retains its viability for long time if taken out of water. C. mrigala is an active bottom dwelling Indian major carp, which lives in relatively clean water and dies shortly after taken out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 37 publications
2
24
0
1
Order By: Relevance
“…There are great variations in the number of gill arches between the different fish species; in the present study there are three pairs of gills in the striped red mullet, as noted in the puffer fisch (Abumandour & Gewaily), however, the four pairs of gills is the common number in most teleost fishes as in the present investigation in the grey gurnard (Hughes & Grimstone, 1965;Hughes & Morgan;Hossler et al, 1985;Eiras-Stofella et al, 2001;Eiras-Stofella & Fank-de-Carvalho, 2002;Zayed & Mohamed;Cinar et al, 2009;Díaz et al, 2009;Kumari et al, 2009;Kumari et al, 2012;Alsafy;Elsheikh). However, there are five pairs of gills, but the fifth pair is ill developed and devoid from any gill filaments as noted in catfish (Zayed & Mohamed;Kumari et al, 2005;Elsheikh), in contrast, in Senegal sole (Arellano et al, 2004) reported that the fifth pair is well-developed and contains gill filaments.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…There are great variations in the number of gill arches between the different fish species; in the present study there are three pairs of gills in the striped red mullet, as noted in the puffer fisch (Abumandour & Gewaily), however, the four pairs of gills is the common number in most teleost fishes as in the present investigation in the grey gurnard (Hughes & Grimstone, 1965;Hughes & Morgan;Hossler et al, 1985;Eiras-Stofella et al, 2001;Eiras-Stofella & Fank-de-Carvalho, 2002;Zayed & Mohamed;Cinar et al, 2009;Díaz et al, 2009;Kumari et al, 2009;Kumari et al, 2012;Alsafy;Elsheikh). However, there are five pairs of gills, but the fifth pair is ill developed and devoid from any gill filaments as noted in catfish (Zayed & Mohamed;Kumari et al, 2005;Elsheikh), in contrast, in Senegal sole (Arellano et al, 2004) reported that the fifth pair is well-developed and contains gill filaments.…”
Section: Discussionsupporting
confidence: 49%
“…Moreover, in freshwater fish Prochilodus scrofa Steindachner and in seawater Eugerres brasilianus, the gill filaments are shorter on both extremities of gill arch and in the strong curvature angle region (Eiras-Stofella & Charvet-Almeida, 1998, 2000, however, Kumari et al, (2012) in catfish and Carp reported that, the length of the gill filaments is shorter on one side than on the other corresponding side of the gill arch.…”
Section: Discussionmentioning
confidence: 95%
“…There are great variations in the number of gills between the different fish species; in the present study there are three pairs of gills, however, four pairs of gills is the common number in most teleost fishes (Hughes & Grimstone, 1965;Hughes & Morgan;Hossler et al, 1985;Eiras-Stofella et al, 2001;Eiras-Stofella & Fank-deCarvalho, 2002;Zayed & Mohamed;Cinar et al, 2009;Díaz et al, 2009;Kumari et al, 2009Kumari et al, , 2012Alsafy;Elsheikh). However, there are five pairs of gills but the fifth pair is ill developed and devoid from any gill filaments as noted in catfish (Zayed & Mohamed;Kumari et al, 2005;Elsheikh), in contrast, in Senegal sole (Arellano et al, 2004) reported that the fifth pair is well-developed and contain gill filaments.…”
Section: Discussionmentioning
confidence: 47%
“…Moreover, in freshwater fish Prochilodus scrofa Steindachner and in seawater Eugerres brasilianus, the gill filaments are shorter on both extremities of gill arch and in the strong curvature angle region (Eiras-Stofella & Charvet-Almeida, 1998, 2000, however (Kumari et al, 2012) in catfish and Carp reported that, in gill arch the length of gill filaments is shorter on one side than the other.…”
Section: Discussionmentioning
confidence: 96%
“…Mucus is trapped and held within the microridges. The mucus layer on the gill surface may (1) reduce the abrasive action of suspended particles in water during ventilation (Kumari, Mittal, & Mittal, ; Moron & Fernandes, ), (2) be involved in osmoregulatory processes through the trapping of ions from freshwater (Monteiro, Oliveira, Fontainhas‐Fernandes, & Sousa, ), and/or (3) be implicated in the immune/barrier system. Several defense factors have been identified in mucus (immunoglobulins, lectin, lysozyme, and complement, etc.)…”
Section: Discussionmentioning
confidence: 99%